2022
DOI: 10.1111/nph.18593
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative interactions between nitrogen fixation and phosphorus nutrition in legumes

Abstract: Summary Legumes such as soybean are considered important crops as they provide proteins and oils for humans and livestock around the world. Different from other crops, leguminous crops accumulate nitrogen (N) for plant growth through symbiotic nitrogen fixation (SNF) in coordination with rhizobia. A number of studies have shown that efficient SNF requires the cooperation of other nutrients, especially phosphorus (P), a nutrient deficient in most soils. During the last decades, great progress has been made in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 157 publications
0
15
0
1
Order By: Relevance
“…Furthermore, the plant species with different strategies for phosphorus mining may contribute to the variations of SNF rate. The phosphatase around plant roots can efficiently gain phosphorus in phosphorus‐deficient soils (Zhong et al., 2022), while phosphatase activity is generally specialized for plant species (Guilbeault‐Mayers et al., 2020). The host plant species with high phosphatase activity fix more N (2.3 μmol N 2 m −2 h −1 of Inga punctata ) in contrast to that of low phosphatase activity (0.5 μmol N 2 m −2 h −1 of Erythrina fusca ; Batterman et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the plant species with different strategies for phosphorus mining may contribute to the variations of SNF rate. The phosphatase around plant roots can efficiently gain phosphorus in phosphorus‐deficient soils (Zhong et al., 2022), while phosphatase activity is generally specialized for plant species (Guilbeault‐Mayers et al., 2020). The host plant species with high phosphatase activity fix more N (2.3 μmol N 2 m −2 h −1 of Inga punctata ) in contrast to that of low phosphatase activity (0.5 μmol N 2 m −2 h −1 of Erythrina fusca ; Batterman et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The deficit phosphorus also hampers SNF because phosphorus is the indispensable element for symbiosis (e.g. the biosynthesis of ribosomes, proteins and phospholipids; Zhong et al., 2022). The SNF rates of Medicago sativa are increased from 1.8 to 3.3 μmol C 2 H 4 plant −1 h −1 with the addition of 0.13 mg phosphorus g −1 soil (Crews, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the growth and N and P contents are increased in soybean after inoculating with rhizobia in low-P acid soils (Cheng et al, 2009). A variety of PSI genes and proteins have been identified in nodules exposed to P deficiency (Figure 2; Hernańdez et al, 2009;Chen et al, 2011;Cabeza et al, 2014;Xue et al, 2018;Zhong et al, 2023). For example, 1140 and 2055 genes have been found to be regulated by P deficiency in nodules of M. truncatula and soybean, respectively (Cabeza et al, 2014;Xue et al, 2018).…”
Section: Symbiotic Association With Soil Microorganismsmentioning
confidence: 96%
“…Unlike most other non-legume plants, legumes can develop symbiotic interaction with rhizobia to form nodules that can fix atmospheric N, thereby contributing to enhance agricultural sustainability (Abdelrahman et al, 2018;Yang et al, 2022). Since symbiotic N fixation (SNF) in nodules requires significant inputs of energy, legumes are generally considered to have a high P requirement (Sulieman and Tran, 2015;Pang et al, 2018b;Zhong et al, 2023). Furthermore, as N-fixing root nodules are strong P sinks, the growth and yield of legumes are dramatically decreased by 30-40% under low P stress (Tesfaye et al, 2007;Valdeś-Loṕez and Hernańdez, 2008;Chen et al, 2011;Qin et al, 2012;Guo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Legumes induce high rhizosphere priming, even if substantial variation between species can be observed (Henneron, Kardol, et al, 2020). Legumes may also rely on rhizosphere priming for the acquisition of other nutrients such as phosphorus, which are potentially limiting for plant growth and N 2 fixation (Zhong et al, 2023). Exudation of carboxylates is considered one of the key mechanisms for P uptake when P is sparingly soluble in soils and the role of carboxylate exudation has been shown to be crucial for the P nutrition of legumes (Weisskopf et al, 2006).…”
Section: Introductionmentioning
confidence: 99%